Penerapan Konsep Salafiyah Dalam Sistem Ibadah Santri Pendidikan di Pondok Pesantren Tarbiyah Islamiyah At-Taqwa Candung - Nadia Putri Wulandari; Puti Andam Dewi; Irfan Fauzi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research aims to understand how Salafiyah principles are applied in the daily worship practices of students, including prayer, recitations (reading the Koran), dhikr, and other acts of worship. The research methods used were participatory observation and interviews with students as well as analysis of relevant documents. The research results show that Salafiyah principles play an important role in shaping the daily worship patterns of santri, with an emphasis on a sincere and valid understanding of Islamic teachings based on the Salafus Salih (early generation of Islam). The daily worship of the students at the Islamic boarding school. At-Taqwa Canduang Islamic Boarding School uses the Salafiyah curriculum which is designed to ensure an authentic Islamic scientific heritage and teach an understanding of Islam that is in accordance with the understanding of the Salaf. The teachings adhered to by Islamic boarding schools are Aqidah (imam al-Ash’ari), Fiqh (imam Shafi’i), Sufism (imam Al-Ghazali). The advantage of implementing the salafiyah concept is that the boarding school has the freedom to choose and determine the curriculum according to the portions and proportions desired by the boarding school.Besides that, book learning is more dominant and has priority over general education. Disadvantages in implementing the salafiyah concept. Because the salafiyah program is still new, in the sense that it has only become a unit of equality education, of course the regulations that govern and the institutions that protect these salafiyah lodges are not yet as complete and comprehensive as madrasas. Obstacles to implementing the salafiyah concept include: the salafiyah curriculum not yet as complete as the madrasa curriculum, this makes it difficult for boarding school managers to guide an ideal and effective system of governance and curriculum development. Likewise at the At-Taqwa Canduang Islamic boarding school due to the many shortcomings in terms of facilities and factors that support the development of the Islamic boarding school.